2009
DOI: 10.1017/s1368980009005084
|View full text |Cite
|
Sign up to set email alerts
|

Low calcium intake is associated with increased bone resorption in postmenopausal Japanese women: Yokogoshi Study

Abstract: Objective: Low Ca intake is common among Japanese women, but its effect on bone metabolism has not been fully elucidated. The aim of the present study was to determine the relationship between Ca intake and serum markers of bone turnover in postmenopausal Japanese women. Design: A cross-sectional study. Setting: A community setting. Subjects: Subjects were 595 home-dwelling postmenopausal Japanese women. Ca intake was assessed by a validated FFQ. Serum type I collagen cross-linked N-telopeptides (NTX) and oste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 22 publications
0
6
0
2
Order By: Relevance
“…Increased bone turnover is found in postmenopausal women with low calcium intake 19. Although the effect of calcium supplements on serum bone turnover markers like osteocalcin and NTX was not definitively demonstrated with this trial, serum osteocalcin and NTX concentrations showed a tendency to decrease more in the calcium supplement groups than the placebo group.…”
Section: Discussionmentioning
confidence: 56%
“…Increased bone turnover is found in postmenopausal women with low calcium intake 19. Although the effect of calcium supplements on serum bone turnover markers like osteocalcin and NTX was not definitively demonstrated with this trial, serum osteocalcin and NTX concentrations showed a tendency to decrease more in the calcium supplement groups than the placebo group.…”
Section: Discussionmentioning
confidence: 56%
“…In the USA, the mean intake of calcium in women after age 55 is only ~600 mg/day [ 61 ]. Daily consumption of ~500 mg by elderly Japanese women [ 89 ] is far below a recommended level of 1,200 mg, although daily calcium requirements of East Asian populations may be lower for ethnic reasons [ 79 ].…”
Section: Inadequate Calcium Intake: a World-wide Problemmentioning
confidence: 99%
“…This finding may explain the increased prevalence of low bone density in morbidly obese subjects [42]. This is not the case in nonobese subjects, as a Japanese study described an inverse correlation between these variables [40]. There are very few studies that have evaluated NTX-s in obese and morbidly obese individuals, and thus, our data is new, but needs further confirmation.…”
Section: Discussionmentioning
confidence: 63%